Perceptions of the Role of Short-Term Volunteerism in International Development: Views from Volunteers, Local Hosts, and Community Members. (12th June 2016) - Loiseau, Bethina; Sibbald, Rebekah; Raman, Salem A.; Darren, Benedict; Loh, Lawrence C.; Dimaras, Helen
Abstract : Background. Short-term international volunteer trips traditionally involve volunteers from high-income countries travelling to low- and middle-income countries to assist in service-related development activities. Their duration typically ranges from 7 to 90 days. The city of La Romana, Dominican Republic, receives hundreds of short-term international volunteers annually. They participate in activities aimed at improving conditions faced by a marginalized ethnic-Haitian community living in bateyes. Methods. This qualitative analysis examined perceptions of short-term international volunteerism, held by three key stakeholder groups in La Romana: local hosts, international volunteers, and community members. Responses from semistructured interviews were recorded and analysed by thematic analysis. Results. Themes from the 3 groups were broadly categorized into general perceptions of short-term volunteerism and proposed best practices. These were further subdivided into perceptions of value, harms, and motivations associated with volunteer teams for the former and best practices around volunteer composition and selection, partnership, and skill sets and predeparture training for the latter. Conclusion. Notable challenges were associated with short-term volunteering, including an overemphasis on the material benefits from volunteer groups expressed by community member respondents; misalignment of the desired and actual skill sets of volunteers; duplicate and uncoordinated volunteer efforts; and the perpetuation of stereotypes suggesting that international volunteers possess superior knowledge or skills. Addressing these challenges is critical to optimizing the conduct of short-term volunteerism.